Currency Unions, Trade, and Heterogeneity - Natalie Chen; Dennis Novy (Center for Economic Studies and ifo Institute (CESifo), 2018)
How do trade costs affect international trade? This paper offers a new approach. We rely on a flexible gravity equation that predicts variable trade cost elasticities, both across and within country pairs. We apply this framework to the effect of currency unions on international trade. While we estimate that currency unions are associated with a trade increase of around 38 percent on average, we find substantial underlying heterogeneity. Consistent with the predictions of our framework, we find effects around three times as strong for country pairs associated with small import shares, and a zero effect for large import shares. Our results imply that conventional homogeneous currency union estimates do not provide helpful guidance for countries considering to join a currency union. Instead, countries need to take into account the distribution of their trade shares to assess the impact of trade costs.
Keywords: F14; F15; F33; 330; currency unions; euro; gravity; heterogeneity; trade costs; trade elasticity; translog